Epicauta vittata (Fabricius): occurrence in tomato plant and weeds in the State of Rondônia - Turcato, Claudemir Schwanz; Toledo, Freddy Melo; Sampaio, Emanoel Pereira; Alves, Cleiton Dias; Rondelli, Vando Miossi; Dias, Jairo Rafael Machado; Souza, Fábio Régis de (EntomoBrasilis, 2020)
The tomato (Solanum lycopersicum L.) plant stands out for being a species cultivated throughout the national territory, being the most important vegetable in Brazil, from the socioeconomic point of view. However, it has been one of the crops most affected by phytosanitary problems. For example, there are the pest insects of the genus Epicauta (Coleoptera: Meloidae). Thus, the objective of this study was to record the occurrence of a pest insect (beetle) harming vegetative growth and productive performance in the fresh-market tomato crop and feeding on weeds. The tomato plants were found on “jurubeba” (Solanum paniculatum L.) rootstock, spaced 1.0 m x 0.5 m, grown in the municipality of Rolim de Moura, Rondônia state. The insect-pest (beetle) was identified as Epicauta vittata (Fabricius). It was observed that the damages caused by the larvae occurred in the main stem of the tomato, only above the grafting site, causing boring, however no damage was observed in the rootstock (“jurubeba”). Adult insects caused defoliation in both tomato plant and joyweed (Alternanthera tenella Colla), slender amaranth (Amaranthus viridis L.), “trapoeraba” (Commelina benghalensis L.) and morning glory (Ipomoea purpurea [L.]). High population of E. vittata causes severe damages to tomato, damaging the vegetative growth and productive performance of the crop, however does not affect the root system when grafted with “jurubeba” (S. paniculatu). Epicauta vittata in the adult phase is fed alternately of weeds.